2018
DOI: 10.1186/s40068-018-0121-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorous status and adsorption characteristics of acid soils from Cheha and Dinsho districts, southern highlands of Ethiopia

Abstract: Background: Though soils in the study areas are characterized by higher iron and aluminum oxides, and low available P contents, study on P adsorption characteristics is limited. The purpose of this experiment was to evaluate adsorption properties of selected soils and determine the standard phosphorous requirements of the soils. In this experiment, separately weighed 2 g soil samples were equilibrated in 50 ml of 0.01 M CaCl 2 solution containing KH 2 PO 4 at rates of 0, 1, 2.0, 4.0, 8.0, 16.0, 24.0, and 32.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 62 publications
3
22
3
Order By: Relevance
“…Levels of TOC, TN, Pav, Kav, Caav, Mgav, Mnav and Feav were surprisingly high inside the enset gardens, much higher than typical values reported in literature (Ayenew et al, 2018;Elias;2017;Hengl et al, 2017;Mamo et al, 2014;Mamo et al, 2002;Moges and Holden, 2008;Nabhan et al, 1999;Roy et al, 2006). The pH measured in the enset gardens is comparable to the optimum range suggested for enset, i.e.…”
Section: Soil Fertility In Relation To Agro-ecology and Management Prcontrasting
confidence: 46%
“…Levels of TOC, TN, Pav, Kav, Caav, Mgav, Mnav and Feav were surprisingly high inside the enset gardens, much higher than typical values reported in literature (Ayenew et al, 2018;Elias;2017;Hengl et al, 2017;Mamo et al, 2014;Mamo et al, 2002;Moges and Holden, 2008;Nabhan et al, 1999;Roy et al, 2006). The pH measured in the enset gardens is comparable to the optimum range suggested for enset, i.e.…”
Section: Soil Fertility In Relation To Agro-ecology and Management Prcontrasting
confidence: 46%
“…Soil solution P at the level of 0.2 mg P L −1 is sufficient for optimum yield (Naeem et al 2013;Mihoub et al 2019). Mihoub et al (2016) and Ayenew et al (2018) reported that several crops achieved maximum growth at 0.2 and 0.32 mg P L −1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Soil solution P at the level of 0.2 mg P L −1 was sufficient for optimum yield (Mihoub et al 2019;Naeem et al 2013). Ayenew et al (2018) reported that several crops achieve maximum growth at 0.2 and 0.32 mg P L −1 . Mehdi et al (2007) proposed 0.252 mg P L −1 soil solution as optimum P level for wheat production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption curves provide an adequate basis for estimation of P requirements across a diversity of soils and environment at constant temperature and pressure (Islam, 2014 andKruse et al, 2015). However, limited work has been carried out to evaluate the relationship between the P adsorption capacity and specific soil properties in the research areas and generally in Ethiopia (Chimdi et al, 2013;(Wogi et al, 2015;Haile andWolde, 2015 andAyenew et al, 2018). Thus, the objectives of this study were: (i) to quantify P adsorbed and compare the applicability of Langmuir and Freundlich equations in describing the adsorption of P in acidic soils of Tsegede highlands and (ii) to evaluate the relationships between P adsorption properties of the acidic soils across Tsegede highlands.…”
Section: Introductionmentioning
confidence: 99%